PANDEMI COVID-19 INDONESIA: KAJIAN PEMIKIRAN, KEBIJAKAN RITUAL IBADAH, DAN EKONOMI ISLAM (MAQASID ASY-SYARIAH) - Rahman, Azibur; Pujianto, Wahyu Eko; Salmon, Indra Pratama Putra (Jurnal Studi Agama dan Masyarakat, 2021)
Since Covid-19 pandemic occurred, the government and authorities in Indonesia have restricted almost all community activities in Indonesia, including various activities in houses of worship having an impact on the socio-economic vulnerability of Muslims. This study was to describe the phenomenon of the condition of Muslims affected by the pandemic, by providing a Muslim perspective as well as explaining how Islam responds to the epidemic phenomenon, restriction policies, and socio-economics. This study applied a literature study with a qualitative approach to obtain descriptive and qualitative analytical data. The data were collected through reviewing literature and data about the current situation of Covid -19 pandemic and the ongoing dynamics of Muslim people. This study was a literature study collaborating between Islamic perspectives with contemporary phenomena and theories so that they contributed to strengthening the argument that Islam and its experiences were still very relevant to today's conditions. The result showed that: first, Islam provided jabariyah and qadariyah perspectives for Muslims in responding to the pandemic phenomenon; second, Islam provided relevant perspectives in policy formulation during the pandemic, and; third, Islam emphasized that Maqasid Asy-Sharia was a strategy and concept in overcoming the economic vulnerability of the community during and after the pandemic.